2006
DOI: 10.3892/or.15.4.1027
|View full text |Cite
|
Sign up to set email alerts
|

Computational vision systems for the detection of malignant melanoma

Abstract: Abstract. In recent years, computational vision-based diagnostic systems for dermatology have demonstrated significant progress. We review these systems by first presenting the installation, visual features utilized for skin lesion classification and the methods for defining them. We also describe how to extract these features through digital image processing methods, i.e. segmentation, registration, border detection, color and texture processing, and present how to use the extracted features for skin lesion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…Reference Used Databases [13] Melanoma vs. Clark Nevus [16] Melanoma vs. Nevus [22] Melanoma vs. Dysplastic Nevus [25] Melanoma vs. Nevus This proposal Melanoma and Dysplastic Nevus vs. 5 kinds of Nevus…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reference Used Databases [13] Melanoma vs. Clark Nevus [16] Melanoma vs. Nevus [22] Melanoma vs. Dysplastic Nevus [25] Melanoma vs. Nevus This proposal Melanoma and Dysplastic Nevus vs. 5 kinds of Nevus…”
Section: Discussionmentioning
confidence: 99%
“…Mean and variance of the gradient are the features applied in order to discriminate between the two classes when evaluating the radius evolution. The second group is also composed of geometric features [22]. These features are obtained applying the formulas below:…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these methods try to imitate the ABCD rule of dermoscopy where asymmetry is quantified with respect to a symmetry axis that bisects the lesion. In automatic image analysis approaches, the symmetry axis is determined in a variety of ways, such as principal axes (moment) of inertia of the lesion shape [52]. The asymmetry is then quantified by overlapping the two halves of the lesion along the symmetry axes and dividing the nonoverlapping area differences of the two halves by the total area of the lesion [5256].…”
Section: Colour Asymmetrymentioning
confidence: 99%
“…In the review [52] authors surveyed computer-based systems according to acquisition, feature definition, extraction and skin lesion classification. Authors concluded that some widely used lesion parameters like lesion size, shape, color, and texture do not correspond to known biological phenomena and the structural patterns that are considered essential for manual lesion categorization are absent in the analysis due to their complexity.…”
Section: Related Workmentioning
confidence: 99%